2022
DOI: 10.1007/s12282-022-01377-7
|View full text |Cite
|
Sign up to set email alerts
|

Internal mammary lymph node metastasis in breast cancer patients based on anatomical imaging and functional imaging

Abstract: Internal mammary lymph node (IMLN) metastasis forms part of the clinical node classification for primary breast cancer, which influences the treatment strategy. However, because of the IMLNs’ complicated anatomical structures and relationships with adjacent structures, IMLN biopsy or resection is associated with a limited improvement in prognosis and a high complication rate. The positivity rate also varies broadly according to imaging modality, and there is a low rate of agreement between the imaging and path… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 89 publications
0
2
0
Order By: Relevance
“… 14,19 However, higher ADC 0 and lower K in the luminal subtype was reported in another recent study. 20 This study also suggested improved diagnostic performance by combining DKI parameters with parameters obtained from dynamic contrast-enhanced MRI.…”
Section: Clinical Applicationsmentioning
confidence: 72%
“… 14,19 However, higher ADC 0 and lower K in the luminal subtype was reported in another recent study. 20 This study also suggested improved diagnostic performance by combining DKI parameters with parameters obtained from dynamic contrast-enhanced MRI.…”
Section: Clinical Applicationsmentioning
confidence: 72%
“…In the context of breast cancer, the presence of sternal or parasternal swelling is usually a clinical indicator of advanced internal mammary chain (IMC) node involvement [ 9 ]. Due to the anatomical position, these lymph nodes are not palpable on clinical examination and their involvement is usually found on radiological investigation or surgical intervention for a known breast cancer case [ 10 ].…”
Section: Introductionmentioning
confidence: 99%